Neonatal Transfusion Practices - Sesok-Pizzini, Deborah A. (Springer International Publishing : Imprint: Springer, 2017)
This book provides a concise yet comprehensive review of neonatal transfusion medicine. The text covers major areas of the field, including chapters dedicated to pre transfusion testing, manufacturing, standards and storage; blood product administration; special congenital and acquired disorders in the neonate; hemolytic disease of the newborn; intrauterine transfusions; adverse reactions; and ECMO. The volume features contributions from a diverse group of experts in the field and include pathologists, anesthesiologists, neonatologists, a pediatric hematologist and oncologist, and a high-risk obstetrician. These authors contribute their unique expertise and perspectives to the practice of neonatal transfusion medicine and allow the reader to experience an in depth introduction to each of the chapter topics. Neonatal Transfusion Practices is a valuable, go-to reference that addresses some of the more frequent questions asked by clinicians and professionals who have limited exposure to neonatal transfusion practices. .
Keywords: Medicine.; Blood transfusion.; Hematology.; elektronické knihy; electronic books